2002
DOI: 10.1203/00006450-200203000-00014
|View full text |Cite
|
Sign up to set email alerts
|

CoASH and CoASSG Levels in Lungs of Hyperoxic Rats as Potential Biomarkers of Intramitochondrial Oxidant Stresses

Abstract: Coenzyme A (CoASH) is compartmentalized preferentially in the mitochondria, and CoASH and its mixed disulfide with glutathione (CoASSG) undergo thiol/disulfide exchange reactions with glutathione (GSH) and glutathione disulfide (GSSG) in vitro. We measured CoASH and CoASSG in freeze-clamped lung tissues from Fischer-344 and Sprague-Dawley rats maintained in room air or exposed to Ͼ95% O 2 for 48 h to test the hypothesis that oxidant stresses on lung thiol status would be observed in the CoASH/CoASSG redox coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
3
13
1
Order By: Relevance
“…The losses in CoASH are not offset by increases in CoASSG, as might have been expected with a simple redox shift, but the data presently available do suggest that the decreases in lung CoASH levels represent some form of secondary oxidant stress response. Fasting for 48 h caused declines in lung GSH concentrations and contents and in GSSG contents, in contrast with what we have observed in exposure of these animals to hyperoxia (28).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The losses in CoASH are not offset by increases in CoASSG, as might have been expected with a simple redox shift, but the data presently available do suggest that the decreases in lung CoASH levels represent some form of secondary oxidant stress response. Fasting for 48 h caused declines in lung GSH concentrations and contents and in GSSG contents, in contrast with what we have observed in exposure of these animals to hyperoxia (28).…”
Section: Discussioncontrasting
confidence: 99%
“…The decreases in lung CoASH contents we observed in previous studies of rats exposed to Ͼ95% O 2 (28) do not seem to be mediated by diminished food intake caused by exposure of the animals to hyperoxia. Thus, the effects of hyperoxia on lung CoASH contents are more attributable to other effects of hyperoxia.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The rats exposed to 90% O 2 had the highest 2,3-DHBA and the highest lung wet weight. This finding is consistent with previous studies that have demonstrated that a hallmark of hyperoxic lung injury is pulmonary edema (13,35,36). It is of interest to note that the rats exposed to 90% O 2 ϩ 100 ppm NO had the greatest lung wet weight but did not have the greatest 2,3-DHBA.…”
Section: Discussionsupporting
confidence: 92%
“…Coenzyme A (CoASH) and its disulfide with GSH (CoASSG), primary compartmentalized within mitochondria, have been measured and utilized as a marker of mitochondrial specific redox status [61,62]. GSSG levels have been found to increase as early as 4 hours post-SE in the cortex [24].…”
Section: Oxidative Stress and Mitochondrial Involvement In Experimentmentioning
confidence: 99%